2019
DOI: 10.1093/icvts/ivz046
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of planning coronary artery bypass grafting based only on coronary computed tomography angiography and CT-derived fractional flow reserve: a pilot survey of the surgeons involved in the randomized SYNTAX III Revolution trial

Abstract: OBJECTIVES Invasive coronary angiography has been the preferred diagnostic method to guide the decision-making process between coronary artery bypass grafting (CABG) and percutaneous coronary intervention and plan a surgical revascularization procedure. Guidelines recommend a heart team approach and assessment of coronary artery disease (CAD) complexity, objectively quantified by the anatomical SYNTAX score. Coronary computed tomography angiography (CCTA) and CT-derived fractional flow reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…6 In preparation of this first-in-man study, five cardiac surgeons initially involved in the SYNTAX III Revolution trial were asked to review retrospectively the randomised cases allocated to surgery and to decide on an individual basis whether the surgical planning of the cases was feasible based on the sole evaluation of CCTA and FFR CT . 18 In this survey, cardiac surgeons agreed in 84% of cases to plan and perform CABG solely guided by the CCTA information including FFR CT . It means that in 16% of the cases, the surgeon required the viewing of ICA.…”
Section: Statistical Considerationmentioning
confidence: 85%
“…6 In preparation of this first-in-man study, five cardiac surgeons initially involved in the SYNTAX III Revolution trial were asked to review retrospectively the randomised cases allocated to surgery and to decide on an individual basis whether the surgical planning of the cases was feasible based on the sole evaluation of CCTA and FFR CT . 18 In this survey, cardiac surgeons agreed in 84% of cases to plan and perform CABG solely guided by the CCTA information including FFR CT . It means that in 16% of the cases, the surgeon required the viewing of ICA.…”
Section: Statistical Considerationmentioning
confidence: 85%
“…After the SYNTAX III Revolution trial demonstrated the feasibility to provide treatment recommendation for invasive therapy based on coronary computed tomography (CT) imaging in patients with triple-vessel disease, 21 the same group demonstrated in 2019 that surgeons are able to plan CABG surgery based on the sole availability of CT coronary images in the majority of cases (80%). 22 A trial to test its practical feasibility is underway.…”
Section: New Tools For the Diagnosis And Treatment Of Coronary Arterymentioning
confidence: 99%
“…С другой стороны, использование в качестве стандарта инвазивной КАГ уже применялось в более ранних шкалах оценки ПТВ (например, в шкале Diamond-Forester) и вследствие влияния отбора больных, в конечном счете, существенно завышала вероятность наличия ИБС. При настоящем уровне развития диагностических технологий данное противоречие пока не разрешено, но в перспективе решение проблемы видится в использовании неинвазивной оценки состояния коронарного русла с помощью более точных методов МСКТ-ангио-графии коронарных артерий с неинвазивным определением значимости коронарных стенозов [24,25].…”
Section: новая шкала оценки предтестовой вероятностиunclassified